A boron-doped coordination unsaturated Ni-N 3 Type single atom catalyst and preparation method and application thereof

By introducing boron atoms into the single-atom catalyst, the boron doped coordination unsaturated Ni-N3 type single-atom catalyst was prepared, which solved the problem of insufficient CO2 photoreduction activity in the prior art, and achieved higher photocatalytic reduction CO2 activity and selectivity.

CN116237079BActive Publication Date: 2025-04-22NINGBO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211615990.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-15
Publication Date
2025-04-22
Estimated Expiration
2042-12-15

AI Technical Summary

Technical Problem

The existing single-atom catalyst Ni-N-C has insufficient photoreduction activity in CO2, making it difficult to effectively improve the activity and selectivity of photocatalytic reduction of CO2.

Method used

By introducing foreign boron atoms, a boron doped coordination unsaturated Ni-N3 type single atom catalyst is prepared, which consists of a porous nitrogen-rich carbon support and a nickel metal single atom anchored on the support. The coordination environment of the nickel metal single atom is Ni-N3 type structure.

Benefits of technology

The activity and selectivity of boron-doped coordination-unsaturated Ni-N3 type single-atom catalysts in photocatalytic reduction of CO2 have been significantly improved, exceeding the coordination-saturated Ni-N4 structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116237079B_ABST
    Figure CN116237079B_ABST
Patent Text Reader

Abstract

The invention discloses a boron-doped coordinated unsaturated Ni-N3 type single-atom catalyst, which is composed of a porous nitrogen-rich carbon carrier and a nickel metal single atom anchored on the porous nitrogen-rich carbon carrier, and the porous nitrogen-rich carbon carrier is formed by carbonization of ZIF-8, and the coordination environment around the nickel metal single atom is a Ni-N3 type structure. The preparation method of the single-atom catalyst uses metal organic framework material ZIF-8 as a carrier precursor, introduces boron atoms during the synthesis process, and provides an additional opportunity to change the electronic structure of the central metal site to form an unsaturated Ni-N3 structure, and then obtains a boron-nitrogen-doped porous nitrogen-rich carbon carrier through high-temperature pyrolysis, and then introduces nickel salts, and obtains a boron-doped coordinated unsaturated Ni-N3 type single-atom catalyst through calcination again. In addition to having excellent performance in catalyzing CO2 reduction, the single-atom catalyst has certain market application prospects in terms of adsorption, electrode materials, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a boron-doped coordinated unsaturated Ni-N3 type single-atom catalyst and a preparation method thereof. Background Art

[0002] In the process of industrial civilization development, the consumption of fossil fuels has been increasing every year, which has led to a surge in the concentration of CO2 in the atmosphere. Especially in recent decades, the greenhouse effect caused by the increase in the content of CO2 in the atmosphere has not only endangered the balance of natural ecosystems, but also affected human health and even threatened human survival. As a potential carbon resource, converting CO2 into fuel is a promising approach. Currently, photocatalysis is one of the most promising methods for CO2 conversion. It converts the almost unlimited solar energy in nature into usable chemical energy, realizing the conversion and utilization of CO2 without consuming fossil energy.

[0003] Single-atom-modified carbon-based materials are one of the photocatalysts that have emerged in recent years. Depending on the interaction between metal single atoms and supports, the introduction of single-atom catalysts can significantly affect the photocatalytic reduction of CO2. In general, the embedding of single atoms into light-harvesting supports can change the band structure and electronic structure to adjust their light absorption behavior and charge transfer dynamics. In addition, the surface structure of single-atom catalysts can be easily customized through different metal-support interactions to improve the adsorption and activation capabilities of reactants. Therefore, these advantages of single-atom catalysts provide a so-far unparalleled opportunity to significantly improve photocatalytic activity.

[0004] In recent years, Ni-N x Single-atom metal and nitrogen co-doped carbon (Ni-NC) materials at active sites have been shown to be ideal catalysts for photocatalysis. To enhance their intrinsic photocatalytic activity, directing the coordination environment of the Ni center is critical to promote the kinetics of CO evolution, but it remains challenging. Here, we invented a preparation method to prepare coordination-unsaturated Ni-N3-type single-atom catalysts by introducing foreign boron atoms. Compared with the coordination-saturated Ni-N4 structure, the boron-doped Ni single-atom catalysts have enhanced activity and selectivity for photoreduction of CO2. Summary of the invention

[0005] In view of the problem that the existing single-atom catalyst Ni-NC has insufficient activity in CO2 photoreduction, the present invention provides a boron-doped coordinated unsaturated Ni-N3 type single-atom catalyst and a preparation method thereof and application in photocatalytic reduction of CO2.

[0006] The technical solution adopted by the present invention to solve the above technical problems is: a boron-doped coordinated unsaturated Ni-N3 type single atom catalyst, which consists of a porous nitrogen-rich carbon carrier and a nickel metal single atom anchored on the porous nitrogen-rich carbon carrier, the porous nitrogen-rich carbon carrier is formed by carbonization of ZIF-8, and the coordination environment around the nickel metal single atom is a Ni-N3 type structure.

[0007] Preferably, the mass ratio of the porous nitrogen-rich carbon support to the nickel metal single atom is (100-150):(2-3).

[0008] A method for preparing the above-mentioned boron-doped coordinated unsaturated Ni-N3 type single-atom catalyst comprises the following steps:

[0009] Step 1, add 558 mg Zn(NO3)2·6H2O to 20 mL 99.9% methanol, stir evenly with a magnetic force to obtain a mixed solution A; add 616 mg 2-methylimidazole to 20 mL 99.9% methanol, stir evenly with a magnetic force to obtain a mixed solution B; mix the mixed solution A and the mixed solution B in a volume ratio of 1:1, stir at room temperature for 6 hours to obtain a mixed solution C, centrifuge the mixed solution C, wash the obtained white precipitate with 99.9% methanol for 3 times, and vacuum dry overnight to obtain white powder ZIF-8;

[0010] Step 2, ZIF-8 was added to 50 mL of 99.9% methanol, followed by addition of phenylboric acid, ultrasonication for 10 min, stirring at room temperature for 8 hours, centrifugation, and the resulting powder was washed three times with 99.9% methanol, and vacuum dried overnight to obtain a synthetic product, which was named PhB(OH)2@ZIF-8;

[0011] Step 3: calcine PhB(OH)2@ZIF-8 at high temperature in an inert atmosphere, cool it to room temperature, and obtain a black product. -1 Hydrochloric acid leaching, preferably 1-2 mol·L -1 Then, it was washed with deionized water until neutral and dried to obtain boron-doped nitrogen-rich carbon, which was named BNC;

[0012] Step 4, adding BNC to a nickel salt solution, wherein the molar ratio of the nickel salt to the BNC is (0.005-0.05):1, preferably (0.015-0.02):1, grinding and drying in a mortar to obtain a mixture, then adding 100 mg of ammonium chloride to the mixture for further grinding to obtain a composite material consisting of BNC, nickel salt and NH4Cl, and calcining the composite material at a high temperature under an inert atmosphere to obtain a boron-doped coordinated unsaturated Ni-N3 type single atom catalyst.

[0013] Preferably, the molar ratio of phenylboric acid and ZIF-8 used in step 2 is (0.1-0.5):1, preferably (0.2-0.35):1.

[0014] Preferably, the high temperature calcination in step 3 is carried out at a temperature in the range of 600 to 1000° C., preferably 800 to 900° C., for 2 to 4 hours, in an atmosphere of nitrogen or argon.

[0015] Preferably, the nickel salt used in step 4 is at least one of nickel nitrate, nickel chloride, nickel sulfate, etc.

[0016] Preferably, the high temperature calcination in step 4 is carried out at a temperature in the range of 350 to 550° C., preferably 400 to 500° C., for 1 to 2 hours, in an atmosphere of nitrogen or argon.

[0017] The application of the above-mentioned boron-doped coordinated unsaturated Ni-N3 type single-atom catalyst in photocatalytic reduction of CO2.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] (1) The present invention adjusts the atomic configuration by doping boron, thereby constructing an efficient insoluble catalyst that can be applied to CO2 photoreduction. The boron-doped coordination unsaturated Ni-N3 type single atom catalyst of the present invention is composed of a porous nitrogen-rich carbon support and a nickel metal single atom anchored on the porous nitrogen-rich carbon support, wherein the porous nitrogen-rich carbon support is formed by carbonization of ZIF-8, and the coordination environment around the nickel metal single atom is a Ni-N3 type structure. The optimal local electron density around Ni in the unsaturated Ni-N3 structure can promote the adsorption and conversion of the intermediates COOH* and CO*, and exceeds the coordination saturated Ni-N4 structure in terms of selectivity and activity in the photocatalytic CO2 reduction reaction. Compared with the Ni-N4 structure, the coordination unsaturated Ni-N group in the catalyst of the present invention has a larger local space on the atom for the incorporation of foreign atoms, while not affecting the original unsaturated coordination state.

[0020] (2) The present invention provides a simple method for preparing a post-synthesis metal-substituted boron-doped coordinated unsaturated Ni-N3 type single atom catalyst to achieve the controllable synthesis of nickel metal single atoms with low coordination number anchored on the porous nitrogen-rich carbon formed after carbonization of ZIF-8 as a carrier. Metal particles Ni and defective porous nitrogen-rich carbon are used as the source of single atoms and supporting carriers, respectively. The gaseous HCl produced by the pyrolysis of NH4Cl at low temperature can atomize nickel salts into nickel metal atoms, which are captured in an isolated state on the surface of the porous nitrogen-rich carbon.

[0021] (3) The preparation method of the present invention uses the metal organic framework material ZIF-8 as a carrier precursor, introduces boron atoms during the synthesis process, provides an additional opportunity to change the electronic structure of the central metal site, forms an unsaturated Ni-N3 structure, and then obtains a boron-nitrogen doped porous nitrogen-rich carbon carrier through high temperature pyrolysis, and then introduces nickel salt, and calcined again to obtain a boron-doped coordinated unsaturated Ni-N3 type single atom catalyst. Since ZIF-8 not only has the advantages of a cross-three-dimensional network structure, a large pore size and a high specific surface area, but also the porous nitrogen-rich carbon carrier formed after carbonization can effectively conduct electrons and transport ions, ZIF-8 as a carrier precursor has great potential in preparing highly dispersed, high-loaded and highly stable single atom catalysts. At the same time, the Ni-N3 type single atom catalyst successfully synthesized by the preparation method of the present invention has excellent performance in catalyzing CO2 reduction, and has certain market application prospects in terms of adsorption, electrode materials, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 X-ray diffraction patterns of the precursor ZIF-8 and PhB(OH)2@ZIF-8 prepared in step 1 of Example 1 and Comparative Example 1;

[0023] Figure 2 X-ray diffraction patterns of the single atom catalysts prepared in Example 1 and Comparative Example 1;

[0024] Figure 3 This is a scanning electron microscope image of the precursor ZIF-8 prepared in step 1 of Example 1;

[0025] Figure 4 This is a scanning electron microscope image of the single atom catalyst prepared in Example 1;

[0026] Figure 5 The performance diagram of photocatalytic reduction of CO2 of the single atom catalyst prepared in Examples 10 to 13 under simulated sunlight;

[0027] Figure 6 ICP-OES graphs of B and Ni element contents in the single-atom catalysts prepared in Example 1 and Comparative Example 1;

[0028] Figure 7 Performance diagram of photocatalytic reduction of CO2 of single atom catalysts prepared in Example 1 and Comparative Example 1 under simulated sunlight. DETAILED DESCRIPTION

[0029] The present invention is further described in detail below with reference to the accompanying drawings.

[0030] Example 1: A method for preparing a boron-doped coordinated unsaturated Ni-N3 type single-atom catalyst, comprising the following steps:

[0031] Step 1, add 558 mg Zn(NO3)2·6H2O to 20 mL 99.9% methanol, stir evenly with a magnetic force to obtain a mixed solution A; add 616 mg 2-methylimidazole to 20 mL 99.9% methanol, stir evenly with a magnetic force to obtain a mixed solution B; mix the mixed solution A and the mixed solution B in a volume ratio of 1:1, stir at room temperature for 6 hours to obtain a mixed solution C, centrifuge the mixed solution C, wash the obtained white precipitate with 99.9% methanol three times, and vacuum dry at 60°C overnight to obtain white powder ZIF-8;

[0032] Step 2, add 280 mg ZIF-8 to 50 mL 99.9% methanol, then add 100 mg phenylboric acid, ultrasonicate for 10 min, stir at room temperature for 8 hours, centrifuge, wash the resulting powder with 99.9% methanol three times, and vacuum dry at 60 ° C overnight to obtain a white powdery synthetic product, which is named PhB(OH)2@ZIF-8;

[0033] Step 3: 200 mg PhB(OH)2@ZIF-8 was heated at 5 °C min under argon atmosphere. -1 The mixture was heated to 900℃ and calcined for 3h at a rate of 1 mol·L. After cooling to room temperature, a black product was obtained. -1 The mixture was stirred in hydrochloric acid for 2 h, centrifuged, washed with deionized water until neutral, and dried to obtain boron-doped nitrogen-rich carbon, which was named BNC.

[0034] Step 4: Add BNC to a NiCl2·6H2O solution, wherein the weight percentage of NiCl2·6H2O relative to BNC is 2.0%, grind and dry in a mortar to obtain a mixture, then add 100 mg of ammonium chloride to the mixture for further grinding to obtain a composite material consisting of BNC, NiCl2·6H2O and NH4Cl, and heat the composite material under an argon atmosphere at 5°C·min -1 The catalyst was heated to 500 °C and calcined for 1 h to obtain a boron-doped coordinated unsaturated Ni-N3 type single atom catalyst, named Ni-BNC and marked as material A.

[0035] Preparation of materials B to I corresponding to Examples 2 to 9: The preparation method of materials B to I refers to the preparation method of material A in Example 1, except that the ratio of ZIF-8 and phenylboric acid used in step 2 is different. The specific preparation parameters are shown in Table 1.

[0036] Table 1: Preparation parameters of Examples 2 to 7

[0037]

[0038]

[0039] Preparation of materials J to M corresponding to Examples 10 to 13: The preparation method of materials J to M refers to the preparation method of material A in Example 1, the difference lies in the amount of ammonium chloride used in step 4 and the calcination temperature. The specific preparation parameters are shown in Table 2.

[0040] Table 2: Preparation parameters of Examples 10 to 13

[0041] Example Ammonium chloride / mg Calcination temperature℃ Calcination time / h catalyst Example 10 100 500 1 J Embodiment 11 0 500 1 K Example 12 100 550 1 L Example 13 100 450 1 M

[0042] Preparation of Material N corresponding to Comparative Example 1: Compared with Example 1, the difference is that when preparing Material N, step 2 is skipped, and ZIF-8 is directly heated at 5°C·min in an argon atmosphere. -1 The product was heated to 900 °C and calcined for 3 h at a rate of 1 mol·L -1 The mixture was stirred in hydrochloric acid for 2 h, centrifuged, and then washed with deionized water until neutral. The black powder obtained after drying was porous nitrogen-rich carbon NC. NC and NiCl2·6H2O solution were ground and dried in a mortar, wherein the weight percentage of NiCl2·6H2O relative to NC was 2.0%. Then 100 mg of ammonium chloride was added to the ground mixture for further grinding to obtain a composite material composed of NC, NiCl2·6H2O and NH4Cl. The composite material was heated at 5 °C·min under argon atmosphere. -1 The catalyst was heated to 500 °C and calcined for 1 h to obtain a boron-doped coordinated unsaturated Ni-N3 type single atom catalyst, named Ni-NC and marked as material N.

[0043] The material A obtained in the above-mentioned embodiment 1 and the material N obtained in the comparative example 1 were respectively subjected to a photocatalytic reduction of CO2 activity experiment under visible light irradiation, and the specific steps are as follows:

[0044] (1) Weigh a certain amount of material A and material N, dissolve them in a mixed solution (24 mL acetonitrile, 8 mL H2O, 8 mL triethanolamine) and treat them by ultrasound. Add 30 mg of ruthenium bipyridine as a visible light photosensitizer to the solution after ultrasound and treat it by ultrasound to form a uniform solution.

[0045] (2) The solution obtained in step (1) was transferred to a reactor, the reaction solution and the system were thoroughly evacuated several times to ensure that the air was completely discharged, and then high-purity CO2 was filled in, and the system pressure was 80 kPa;

[0046] (3) A 300 W xenon lamp was placed on the top of the reactor for illumination. The temperature of the reaction solution was maintained at room temperature by a water cooling system. The products in the system were measured using a fully automatic online detector and a gas chromatograph (Agilent 8860 GC system).

[0047] Figure 1 The X-ray diffraction (XRD) patterns of the precursor ZIF-8 and PhB(OH)2@ZIF-8 prepared in step 1 of Example 1 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the XRD pattern of PhB(OH)2@ZIF-8 precursor remains unchanged, indicating that the original framework of ZIF-8 is well preserved after the addition of PhB(OH)2. Figure 2 XRD of the boron-doped unsaturated Ni-N3 type single atom catalyst prepared in Example 1 and the saturated Ni-N4 single atom catalyst prepared in Comparative Example 1. Figure 2 It can be seen that the PXRD spectrum of BNC only shows two characteristic diffraction peaks of amorphous carbon at about 24° and 44°, and similar observations are also found in NC samples.

[0048] Figure 3 This is a scanning electron microscope image (SEM) of the precursor ZIF-8 prepared in step 1 of Example 1. The SEM image shows that ZIF-8 has smooth polyhedral particles of different sizes. Figure 4 This is a scanning electron microscope image of the single atom catalyst prepared in Example 1. Figure 4 The nanostructure morphology of the granular single-atom catalyst can be seen in the figure. The prepared single-atom catalyst maintains the original morphology of ZIF-8 and is composed of rhombic polyhedron particles with rough surfaces.

[0049] Figure 5 The performance diagram of the photocatalytic reduction of CO2 by the single-atom catalysts prepared in Examples 10 to 13 under simulated sunlight is shown in FIG. Figure 5 It can be seen that Example 10 exhibits the best photocatalytic reduction of CO2 performance, which is different from Example 11 and higher than the catalytic activity of Examples 12 and 13.

[0050] Figure 6 ICP-OES graph of B and Ni element contents in the single atom catalysts prepared in Example 1 and Comparative Example 1. Figure 6 It can be seen that the mass ratios of B and Ni in Example 1 are 0.04wt% and 1.81wt% respectively, and the mass ratios of B and Ni in Comparative Example 1 are 0 and 1.66wt% respectively.

[0051] Figure 7 The performance diagram of the photocatalytic reduction of CO2 by the single-atom catalyst prepared in Example 1 and Comparative Example 1 under simulated sunlight is shown in FIG. Figure 7 It can be seen that the Ni-BNC prepared in the present invention exhibits good CO2-CO reduction activity and selectivity in the photocatalytic process, and its product generation rate and effective electron transfer number increase significantly with the increase of illumination time. The photocatalytic reduction CO2-CO yield of the Ni single atom catalyst in Example 1 reaches 37.1 μmol·h -1 , much higher than 21.5 μmol·h in Comparative Example 1 -1 In addition, the photocatalytic reduction of CO2-CO selectivity of the Ni single atom catalyst of Example 1 is also improved compared with that of Comparative Example 1, which further illustrates that the boron-doped coordinated unsaturated Ni-N3 type single atom catalyst prepared by the present invention is anchored on the porous carbon with defective single atom Ni-N3 active sites, and the diffusion of the substrate to the exposed single active site is enhanced to achieve efficient photocatalytic reduction of CO2.

[0052] In the above embodiments and comparative examples, the products were analyzed by Agilent online gas chromatography.

[0053] Gas chromatography analysis conditions: Agilent GC-8860 online gas chromatograph is equipped with a hydrogen ion flame detector (FID) and a thermal conductivity detector (TCD). FID is used to detect CO generated by the reaction, and TCD is used to detect H2 generated by the reaction. Since CO and H2 are the two main products generated in the CO2 reduction process, the target product is CO because of the intense competition between H2 generation and CO2 reduction reaction, resulting in reduced selectivity.

Claims

1. A boron-doped coordinated unsaturated Ni-N3 type single atom catalyst, characterized in that: The single-atom catalyst is composed of a porous nitrogen-rich carbon carrier and a nickel metal single atom anchored on the porous nitrogen-rich carbon carrier, wherein the porous nitrogen-rich carbon carrier is formed by carbonizing ZIF-8, and the coordination environment around the nickel metal single atom is a Ni-N3 type structure. The preparation method of the boron-doped coordinated unsaturated Ni-N3 type single-atom catalyst comprises the following steps: Step 1, add 558 mg Zn(NO3)2·6H2O to 20 mL of 99.9% methanol, stir evenly with a magnetic force to obtain a mixed solution A; add 616 mg 2-methylimidazole to 20 mL of 99.9% methanol, stir evenly with a magnetic force to obtain a mixed solution B; mix the mixed solution A and the mixed solution B in a volume ratio of 1:1, stir at room temperature for 6 hours to obtain a mixed solution C, centrifuge the mixed solution C, wash the obtained white precipitate with 99.9% methanol for 3 times, and vacuum dry overnight to obtain white powder ZIF-8; Step 2, ZIF-8 was added to 50 mL of 99.9% methanol, followed by addition of phenylboric acid, ultrasonication for 10 min, stirring at room temperature for 8 hours, centrifugation, washing with 99.9% methanol for 3 times, and vacuum drying overnight to obtain a synthetic product, which was named PhB(OH)2@ZIF-8; Step 3: calcine PhB(OH)2@ZIF-8 at 900°C in an inert atmosphere, cool to room temperature, and obtain a black product. -1 The product was leached with hydrochloric acid, then washed with deionized water until neutral, and dried to obtain boron-doped nitrogen-rich carbon, which was named BNC. Step 4, adding BNC to a nickel salt solution, wherein the molar ratio of the nickel salt to the BNC is (0.005-0.05):1, grinding and drying in a mortar to obtain a mixture, then adding 100 mg of ammonium chloride to the mixture for further grinding to obtain a composite material consisting of BNC, nickel salt and NH4Cl, and calcining the composite material at a high temperature under an inert atmosphere to obtain a boron-doped coordinated unsaturated Ni-N3 type single atom catalyst.

2. The boron-doped coordinated unsaturated Ni-N3 type single atom catalyst according to claim 1, characterized in that: The mass ratio of the porous nitrogen-rich carbon support to the nickel metal single atom is (100-150):(2-3).

3. The boron-doped coordinated unsaturated Ni-N3 type single atom catalyst according to claim 1, characterized in that: The molar ratio of phenylboronic acid and ZIF-8 used in step 2 is (0.1~0.5):

1.

4. The boron-doped coordinated unsaturated Ni-N3 type single atom catalyst according to claim 1, characterized in that: The high temperature calcination time used in step 3 is 2 to 4 hours, and the atmosphere is nitrogen or argon.

5. The boron-doped coordinated unsaturated Ni-N3 type single atom catalyst according to claim 1, characterized in that: The nickel salt used in step 4 is at least one of nickel nitrate, nickel chloride and nickel sulfate.

6. The boron-doped coordinated unsaturated Ni-N3 type single atom catalyst according to claim 1, characterized in that: The high temperature calcination temperature range used in step 4 is 350~550°C, the time is 1~2h, and the atmosphere is nitrogen or argon.

7. Use of the boron-doped coordinated unsaturated Ni-N3 type single-atom catalyst according to claim 1 or 2 in photocatalytic reduction of CO2.